2014
DOI: 10.1016/j.immuni.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Receptor CXCR6 Controls the Functional Topography of Interleukin-22 Producing Intestinal Innate Lymphoid Cells

Abstract: Interleukin-22 (IL-22) plays a critical role in mucosal defense, although the molecular mechanisms that ensure IL-22 tissue distribution remain poorly understood. We show that the CXCL16-CXCR6 chemokine-chemokine receptor axis regulated group 3 innate lymphoid cell (ILC3) diversity and function. CXCL16 was constitutively expressed by CX3CR1(+) intestinal dendritic cells (DCs) and coexpressed with IL-23 after Citrobacter rodentium infection. Intestinal ILC3s expressed CXCR6 and its ablation generated a selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 53 publications
5
131
1
Order By: Relevance
“…This localization is determined in part through subset‐specific chemokine receptor expression. Localization of NKp46 + ILC3 is dictated by expression of CXCR6 resulting in retention in the lamina propria in response to CXCL16‐producing dendritic cell subsets 91, 92. LTi‐like ILC3 localize to secondary and tertiary lymphoid tissues driven by expression of CXCR5, CCR6 and CCR7 and cluster within interfollicular regions where they are ideally poised to interact with both T and B cells.…”
Section: Ilc3 Interactions With Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…This localization is determined in part through subset‐specific chemokine receptor expression. Localization of NKp46 + ILC3 is dictated by expression of CXCR6 resulting in retention in the lamina propria in response to CXCL16‐producing dendritic cell subsets 91, 92. LTi‐like ILC3 localize to secondary and tertiary lymphoid tissues driven by expression of CXCR5, CCR6 and CCR7 and cluster within interfollicular regions where they are ideally poised to interact with both T and B cells.…”
Section: Ilc3 Interactions With Adaptive Immunitymentioning
confidence: 99%
“…As both subsets of ILC3 produce IL‐22 in the intestine the relative contribution of these two subsets to anti‐bacterial immunity has proven controversial. Initial studies proposed that NCR + ILC3 are important during C. rodentium infection in mice with partial or total immunodeficiency 27, 51, 91, 117. However, NKp46 + ILC3 are dispensable for the control of C. rodentium infection in the presence of T cells 84, 118.…”
Section: Ilc3 In Inflammation and Infectionmentioning
confidence: 99%
“…For stimulation, 1-2 3 10 6 cells were incubated at 37˚C with IL-1b (R&D Systems; 100 ng/ml), IL-2 (PeproTech; 100 ng/ml), IL-6 (R&D Systems; 20 ng/ml), and IL-23 (R&D Systems; 50 ng/ml) in RPMI 1640 medium containing 10% FCS, penicillin (Life Technologies), and streptomycin (Life Technologies) for 1 h. PMA (50 ng/ml) and ionomycin (500 ng/ml) were added together with BD GolgiPlug (BD Pharmingen; 555029) for the last 3 h before analysis of intracellular cytokines by FACS. Quantitative RT-PCR was performed, as previously described (7,10).…”
Section: Isolation Of Lamina Propria Lymphocytesmentioning
confidence: 99%
“…Two ILC3 sublineages have been proposed (4,5): a CCR6 + T-bet 2 subset that includes lymphoid tissue inducer (LTi) cells and a CCR6 2 T-bet + subset that develops postnatally in response to microbial stimulation and gives rise to cells expressing the natural cytotoxic receptor (NCR) NKp46. These two ILC3 subsets share strong functional similarities (6) but occupy distinct niches (7)(8)(9)(10). As such, their respective specific versus redundant roles in mucosal defense remain unclear.…”
mentioning
confidence: 99%
“…4A, 4B). Recently, it has been reported that CX 3 CR1 + DCs can regulate ILC3 numbers in the SI (50). To investigate whether the effect of Flt3L on ILCs was indirectly mediated by DCs, we analyzed mice in which DCs were constitutively ablated by crossing CD11c-Cre mice with mice expressing diphtheria toxin A (DTA) under the control of a loxP flanked stop cassette in the Rosa26 locus (R-DTA).…”
Section: Dcs Are Not Required For Ilc Developmentmentioning
confidence: 99%